2006
DOI: 10.1094/phyto-96-1027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genetic and Virulence Diversity ofMelampsora larici-populinaPopulations on Wild and Cultivated Poplar and Influence of the Alternate Host

Abstract: The aims of this study were, first, to compare the genetic and virulence diversity between populations of the rust fungus Melampsora larici-populina on wild and cultivated poplar stands and, second, to investigate the influence of the presence of the alternate host of the pathogen, larch, on which its sexual reproduction occurs, on these diversities. Nine French M. larici-populina populations collected from poplar trees in autumn and four populations collected from larch trees during the following spring were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 43 publications
3
64
0
Order By: Relevance
“…Moreover, as discussed by Abbo et al (1), wild hosts can also act as a selection pressure which could affect the fitness of M. pinodes isolates. Gerard et al (21) and Frenkel et al (19) showed that an exchange between wild and domesticated plants could exist in nature. Moreover, Peever (40) showed that as wild host populations are generally more diverse, they could influence the genetic structure of the plant pathogen populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as discussed by Abbo et al (1), wild hosts can also act as a selection pressure which could affect the fitness of M. pinodes isolates. Gerard et al (21) and Frenkel et al (19) showed that an exchange between wild and domesticated plants could exist in nature. Moreover, Peever (40) showed that as wild host populations are generally more diverse, they could influence the genetic structure of the plant pathogen populations.…”
Section: Discussionmentioning
confidence: 99%
“…These rust pathogens cause epidemics of Populus species worldwide, especially in European and North American poplar plantations. Such epidemics can lead to premature defoliation and growth loss and can be fatal for young trees after repeated epidemics (Pinon and Frey 2005;Gérard et al 2006). Consequently, Melampsora spp.…”
Section: Introductionmentioning
confidence: 99%
“…Puccinia graminis, the causal agent of stem rust, has caused devastating epidemics wherever wheat is grown (3), and a new highly virulent strain (Ug99) threatens wheat production worldwide (4). Similarly, epidemics of poplar leaf rust, caused by Melampsora spp., is a major constraint on the development of bioenergy programs based on domesticated poplars (5) as a result of the lack of durable host resistance (6,7). Rust fungi are obligate biotrophic parasites with a complex life cycle that often includes two phylogeneticaly unrelated hosts (2).…”
mentioning
confidence: 99%